1 Del. Laws 104 (1797), ch. 43, § 6 - (:unkn) unknown (General Publisher, 1797)
Prohibited “any Negro or Mulatto slave” from carrying guns, swords, pistols, fowling pieces, clubs, or other arms and weapons without the master’s special license.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES